Harnessing the power of neuroplasticity for intervention - Kolb, Bryan; Muhammad, Arif (Frontiers in Human Neuroscience, 2014)
A fundamental property of the brain is its capacity to change with a wide range of experiences including injury. The spontaneous reparative changes that follow injury may reverse some of the nonspecific degenerative changes but without experiential, physiological, or pharmacological assistance, the spontaneous reparative changes rarely lead to significant behavioral restitution. As we learn more about the principles of brain plasticity we are gradually moving towards the development of novel treatments to facilitate behavioral compensation, and perhaps even some recovery, after cortical injury. We review factors that affect synaptic organization in the normal brain, evidence of spontaneous neuroplasticity after injury, and the evidence that factors including postinjury experience, pharmacotherapy, and cell-based therapies, can form the basis of rehabilitation strategies after brain injuries early in life and in adulthood.